Instrumen asesmen matematika untuk mengases kemampuan berpikir kritis siswa dalam menyelesaikan masalah matematika kelas IX - Anwar, Saiful; Sa'dijah, Cholis; Kusumasari, Vita (UNIVERSITAS NEGERI MALANG, 2024)
The aim of this research is to analyse assessment instruments to assess students' critical thinking abilities in solving IX grade mathematics problems. Instrument analysis takes the form of validity, effectiveness and practicality criteria. The research method used in this research is descriptive qualitative. The subject of this research is the IX graders of Al Rifa Ie Gondanglegi Modern Junior High School. The results of the research show that (1) the assessment instrument received a validity score of 3.045, meaning that the assessment instrument is valid and without revision, (2) the assessment instrument received a practicality score of 3.307, so the developed assessment instrument has high practicality score, (3) the increase of the overall average students' score; among case 1 and case 2, it rises 36.89%, while among case 2 and case 3 it rises 17.38%. According to the improvement criteria set by the researcher, that is 33% < E < 66%, it is considered as a moderate rise value. Therefore, the developed assessment instrument conducted by the researcher is considered as effective assessment instrument. In the end, the instrument Is valid, practical and effective so it is suitable to use in the school.